PERAN ISTRI DALAM MANAJEMEN EKONOMI KELUARGA - Raodhatul Jannah (AN-NISA, 2018)
The wife as feminism human being has a strategic role in family economic management that cannot be ignored. Â In this effort, management functions consisting of planning, organizing, directing, and controlling are outlined proportionally by not denying the wife's role with her typical feminist side. The role of wife must be supported through mutual understanding between husband and wife to retain family economic from many problems.